Remyelination in multiple sclerosis from the miRNA perspective - Maciak, Karina; Dziedzic, Angela; Saluk, Joanna (Frontiers in Molecular Neuroscience, 2023)
Remyelination is the process of repairing damaged myelin sheaths, involving microglia, oligodendrocyte precursor cells (OPCs), and oligodendrocytes acting. Multiple sclerosis (MS) disease is characterized by demyelination and neurodegeneration, with no current treatment that improves myelin regeneration. Short, noncoding RNA molecules, microRNAs (miRNAs) regulate gene expression and are believed to play a crucial role in the remyelination process. Studies showed that miR-223 promotes efficient activation and phagocytosis of myelin debris by microglia, which is necessary for remyelination onset. Meanwhile, miR-124 promotes the return of activated microglia to the quiescent state, and miR-204 and miR-219 promote the differentiation of mature oligodendrocytes. Furthermore, miR-138, miR-145, and miR-338 have been shown to be involved in the synthesis and assembly of myelin proteins. Various delivery systems, including extracellular vesicles, hold promise as efficient and noninvasive delivery systems for miRNAs to stimulate remyelination. This article summarizes the biology of remyelination, current challenges, and strategies, highlighting the role of miRNA molecules in potential diagnostic and therapeutic applications.